2016
DOI: 10.5721/eujrs20164920
|View full text |Cite
|
Sign up to set email alerts
|

Assessing in-season crop classification performance using satellite data: a test case in Northern Italy

Abstract: This study investigated the feasibility of delivering a crop type map early during the growing season. Landsat 8 OLI multi-temporal data acquired in 2013 season were used to classify seven crop types in Northern Italy. The accuracy achieved with four supervised algorithms, fed with multi-temporal spectral indices (EVI, NDFI, RGRI), was assessed as a function of the crop map delivery time during the season. Overall accuracy (Kappa) exceeds 85% (0.83) starting from mid-July, five months before the end of the sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 36 publications
(55 reference statements)
0
33
0
2
Order By: Relevance
“…Multitemporal SIs have already demonstrated their efficacy in capturing cropland characteristics [54,65]. For our approach, three SIs were derived as proxies of crop conditions from optical data: Enhanced Vegetation Index (EVI, Equation (1)), Normalized Difference Flood Index (NDFI, Equation (2)), and Red Green Ratio Index (RGRI, Equation (3)).…”
Section: Satellite Data Pre-processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Multitemporal SIs have already demonstrated their efficacy in capturing cropland characteristics [54,65]. For our approach, three SIs were derived as proxies of crop conditions from optical data: Enhanced Vegetation Index (EVI, Equation (1)), Normalized Difference Flood Index (NDFI, Equation (2)), and Red Green Ratio Index (RGRI, Equation (3)).…”
Section: Satellite Data Pre-processingmentioning
confidence: 99%
“…The main objective is to define a classification tree approach for producing a crop map early in the summer season, i.e., around mid-July [54], to support agricultural management in Northern Italy. Spectral features for the winter and summer crop seasons (named synoptic seasonal features) are extracted from the temporal profiles of a set of proxies derived from optical and SAR data.…”
Section: Introductionmentioning
confidence: 99%
“…Crop type separation is a crucial requirement for the planning [1], short-term monitoring [2], management [3], high-throughput phenotyping [4][5][6], and climate change modeling [7] of agricultural areas. Many of these tasks need up-to-date information, in particular before the end of the growing season.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable researches have been conducted on early-season crop type mapping (Azar et al, 2016; Vaudour, Noirot-Cosson & Membrive, 2015; Villa et al, 2015), and there are two vital factors that contribute to early crop identification: the crop calendar and the remote sensing imagery characteristics. Previous early crop identification studies have shown that if crops are separable, high temporal frequency data such as Moderate Resolution Imaging Spectroradiometer (MODIS) can identify crops with a short image time series (Hao et al, 2015; Zhou, Zhang & Townley-Smith, 2013).…”
Section: Introductionmentioning
confidence: 99%